2019
DOI: 10.3390/cells8020129
|View full text |Cite
|
Sign up to set email alerts
|

Control of the Epithelial-to-Mesenchymal Transition and Cancer Metastasis by Autophagy-Dependent SNAI1 Degradation

Abstract: Autophagy, an intracellular degradation process, is essential for maintaining cell homeostasis by removing damaged organelles and proteins under various conditions of stress. In cancer, autophagy has conflicting functions. It plays a key role in protecting against cancerous transformation by maintaining genomic stability against genotoxic components, leading to cancerous transformation. It can also promote cancer cell survival by supplying minimal amounts of nutrients during cancer progression. However, the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 43 publications
(88 reference statements)
5
34
1
Order By: Relevance
“…However, research has con rmed that NST could not cure cancer. On the contrary, starvation makes cancer cells adapt to adverse conditions, and the surviving cells become more aggressive via EMT [5,26]. Our study con rmed that NST and silencing Akt1 promoted the EMT process of PCa cells.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…However, research has con rmed that NST could not cure cancer. On the contrary, starvation makes cancer cells adapt to adverse conditions, and the surviving cells become more aggressive via EMT [5,26]. Our study con rmed that NST and silencing Akt1 promoted the EMT process of PCa cells.…”
Section: Discussionsupporting
confidence: 59%
“…Through these processes, the invasion of cancer cells enhanced, resulting in increased cell invasion [4]. After starvation exposure, cancer cells obtain the invasion and metastasis ability through Epithelial mesenchymal transition (EMT) process [5]. By EMT process, epithelial cells transformed into broblast-like mesenchymal cells in some physiological and pathological process, which signi cantly enhanced the invasion and metastatic ability of cancer cells [6].…”
Section: Introductionmentioning
confidence: 99%
“…The nuclear retention of HECTD1 following LMB treatment did not reduce the expression levels of SNAIL; however, the fact that the IVE-induced accumulation of HECTD1 in the cytoplasm induced the degradation of SNAIL favors the later possibility. In agreement with these observations, a recent study (43) used cellular fractionation and western blot analysis to demonstrate that SNAIL was localized in both the cytosol and the nucleus, and the nuclear localization of SNAIL was reduced following the serum starvation of the cells. Of note, it was also observed that the overexpression of SNAIL inhibited HECTD1 expression.…”
Section: Discussionsupporting
confidence: 55%
“…The transcription factor snail/ slug is well-known for its tumor-promoting influence as a driver in EMT. Induced autophagy of this protein led to control of EMT and metastasis in a HeLa cell model (Zada et al 2019 ) and knockdown of it suppresses ovarian tumor growth (Baldwin et al 2014 ). In lung carcinoma cells this positive influence on tumor progress was clearly correlated to translocation into the nucleus (Perumal et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%